Preventing suicide: a public health approach to a global problem - Pirkis, J; Dandona, R; Silverman, M; Khan, M; Hawton, K (Elsevier, 2024)
Suicide is prevalent in all countries and is largely preventable. The causes of suicide are multiple and varied. Social determinants of suicide are crucial, but to date these have received insufficient policy attention. This paper, which is the first in a Series on taking a public health approach to suicide prevention, argues for a major change in the way we think about suicide and its prevention. This Series paper presents a public health model that emphasises the broad social determinants of suicide and describes a framework through which these might be addressed. We argue for a policy reset that would take national suicide prevention strategies to the next level. Such policies would become whole-of-government endeavours that tackle major social determinants of suicide at their source. We also argue that high-quality data and methodologically rigorous evaluation are integral to this public health approach.